From hormone replacement therapy to regenerative scaffolds: A review of current and novel primary hypothyroidism therapeutics - Heim, Maria; Nixon, Ian J.; Emmerson, Elaine; Callanan, Anthony (Frontiers in Endocrinology, 2022)
Primary hypothyroidism severely impacts the quality of life of patients through a decrease in the production of the thyroid hormones T3 and T4, leading to symptoms affecting cardiovascular, neurological, cognitive, and metabolic function. The incidence rate of primary hypothyroidism is expected to increase in the near future, partially due to increasing survival of patients that have undergone radiotherapy for head and neck cancer, which induces this disease in over half of those treated. The current standard of care encompasses thyroid hormone replacement therapy, traditionally in the form of synthetic T4. However, there is mounting evidence that this is unable to restore thyroid hormone signaling in all tissues due to often persistent symptoms. Additional complications are also present in the form of dosage difficulties, extensive drug interactions and poor patience compliance. The alternative therapeutic approach employed in the past is combination therapy, which consists of administration of both T3 and T4, either synthetic or in the form of desiccated thyroid extract. Here, issues are present regarding the lack of regulation concerning formulation and lack of data regarding safety and efficacy of these treatment methods. Tissue engineering and regenerative medicine have been applied in conjunction with each other to restore function of various tissues. Recently, these techniques have been adapted for thyroid tissue, primarily through the fabrication of regenerative scaffolds. Those currently under investigation are composed of either biopolymers or native decellularized extracellular matrix (dECM) in conjunction with either primary thyrocytes or stem cells which have undergone directed thyroid differentiation. Multiple of these scaffolds have successfully restored an athyroid phenotype in vivo. However, further work is needed until clinical translation can be achieved. This is proposed in the form of exploration and combination of materials used to fabricate these scaffolds, the addition of peptides which can aid restoration of tissue homeostasis and additional in vivo experimentation providing data on safety and efficacy of these implants.